Analisis Kebocoran Tepi pada Glass Ionomer Kaca dengan Penambahan Bioactive Glass Berbasis Silica dari Ampas Tebu - Catur Putri Kinasih; Didin Erma Indahyani; Izzata Barid; Niken Probosari (STOMATOGNATIC - Jurnal Kedokteran Gigi, 2018)
The use of Glass Ionomer Cement (GIC) has some limitation, such as water sensitivity which leads to formation of microleakage due to shrinkage and brittle. Incorporation of 0.04 wt% bioactive glass nano silica (BAG) with GIC enhances its bioactivity to forming hydroxycarbonate apatite (HCA) leading to preventing of marginal gap formation. The objective this study was To determine the difference of microleakage means value between GIC and GIC which has been added by BAG from bagasse. In this study making BAG from bagasse, than choose the samples (24 bovine) randomly and grouping them to be 4 groups, which are group 1, GIC; group 2, GIC+Vaseline, group 3, GIC+BAG; group 4 GIC+BAG+Vaseline. All of the samples are supposed to be preparation, placed of the restoration, and stored in the aquadest then methylen blue 1% in sequence at 37oC until 24 h. The microleakage means value is decided by scoring system depend on the penetration of methylen blue 1% at occlusal wall and gingival wall. The microleakage means value on GIC+BAG is smaller than GIC, but their differences were not significant.